2021
DOI: 10.1093/ckj/sfab017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K supplementation and arterial calcification in dialysis: results of the double-blind, randomized, placebo-controlled RenaKvit trial

Abstract: Background Arterial calcification is associated with cardiovascular mortality in dialysis patients. Active matrix Gla-protein (MGP) is a vitamin K-dependent inhibitor of arterial calcification. Elevated plasma concentrations of inactive MGP, i.e. dephosphorylated-uncarboxylated MGP (dp-ucMGP), is prevalent in dialysis patients. MGP inactivity might contribute to arterial calcification. We investigated if vitamin K supplementation had an effect on arterial calcification in chronic dialysis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 38 publications
1
40
0
4
Order By: Relevance
“…Moreover, the study had a high drop-out rate of 51%, and only 52 patients were ultimately included in the analysis. Similarly, the Effect of Vitamin K2 (MK7) on Cardiovascular and Bone Disease in Dialysis Patients (RenaKvit) RCT [ 87 ] recently reported that daily treatment with 360 μg MK-7 for two years in 21 ESKD patients undergoing either HD or PD failed to show any beneficial effect on aortic stiffness or calcification. The main drawbacks of this study were its small sample size and high drop-out rate; of 641 patients originally assessed, 48 only were enrolled and only 21 ultimately completed the trial.…”
Section: Interventional Studies Of Vitamin K Supplementation On Arter...mentioning
confidence: 99%
“…Moreover, the study had a high drop-out rate of 51%, and only 52 patients were ultimately included in the analysis. Similarly, the Effect of Vitamin K2 (MK7) on Cardiovascular and Bone Disease in Dialysis Patients (RenaKvit) RCT [ 87 ] recently reported that daily treatment with 360 μg MK-7 for two years in 21 ESKD patients undergoing either HD or PD failed to show any beneficial effect on aortic stiffness or calcification. The main drawbacks of this study were its small sample size and high drop-out rate; of 641 patients originally assessed, 48 only were enrolled and only 21 ultimately completed the trial.…”
Section: Interventional Studies Of Vitamin K Supplementation On Arter...mentioning
confidence: 99%
“…MK7 supplementation reduced plasma dp-ucMGP by 17%, 33%, and 46%, respectively. 155 Effects of vitamin K2 on surrogate cardiovascular outcomes have been studied in 4 randomized controlled trials (Table 3 43,126,[156][157][158][159][160] ). A small Polish study in 42 patients with CKD stages 3 to 5 compared 90 mg MK7 together with 10 mg of cholecalciferol with cholecalciferol alone.…”
Section: Vitamin K Supplementationmentioning
confidence: 99%
“…Finally, the RenaKvit trial lowered dp-ucMGP serum levels in dialysis patients by up to 39% via the administration of 360 mg MK7 daily, but failed to observe a significant impact on pulse-wave velocity, coronary artery calcification, or abdominal aortic calcification. 159 A Singaporian ongoing trial also assesses the cardiovascular effects of MK7, 360 mg, given 3 times weekly for a total duration of 18 months to hemodialysis patients. 161 None of the above studies reported any adverse events related to vitamin K supplementation.…”
Section: Vitamin K Supplementationmentioning
confidence: 99%
“…Compared to hemodialysis (HD), patients undergoing peritoneal dialysis (PD) have higher PWV values and wave reflection indices, suggesting a higher CV risk in this population [ 2 ]. Moreover, although several ongoing randomized controlled trials (RCTs) assess various calcification scores as outcomes, we will assess PWV because calcification scores are thought to reflect the final and less dynamic stage of vascular remodeling, whereas PWV might be subjective to change through time [ 3 ]. This is why PWV has served as a potential therapeutic target to ameliorate CV risk in ESKD patients in several trials [ 4 ].…”
Section: Introductionmentioning
confidence: 99%